Psychosocial aspects of obesity in adults with psoriasis: A systematic review. Issue 2 (3rd May 2021) - Pavlova, N.T.; Kioskli, K.; Smith, C.; Picariello, F.; Rayner, L.; Moss‐Morris, R.
Abstract: Background: Excess weight is a common (30%–40%) multifactorial concern that remains understudied in adults with psoriasis. Objectives: This systematic review aimed to synthesise the evidence on the psychosocial factors associated with body weight in psoriasis and to use these findings to inform clinical practice. The review was registered with PROSPERO (registration number: CRD42020201138). Methods: Electronic databases, related reviews and associated reference lists were searched. Observational and experimental studies reporting on the relationship of psychosocial factors to weight‐related outcomes in adults with body mass index (BMI) of ≥30 kg/m 2 and psoriasis were eligible. The methodological quality of the included studies was assessed using the Critical Appraisal Skills Programme (CASP). Results: Eighteen studies were included in the review, the majority of which ( n = 16) examined cross‐sectional associations between psychosocial factors and weight outcomes. Although the strengths of the associations were heterogeneous, most studies confirmed the positive association between high BMI and increased reports of depression and anxiety, impaired quality of life, deteriorated sleep quality, sexual dysfunction, and daily functioning issues. Only four studies were rated as high quality. Conclusions: The current evidence of the association between psychosocial factors and weight‐related outcomes is largely cross‐sectional with unclear directionality of causality. Longitudinal studies are needed to examine the replicability and generalisability of the examined obesity‐related psychosocial factors in psoriasis. Theoretical exploration of subgroup differences and similarities may pave the way towards intervention personalisation, and ultimately, improved patient outcomes. Abstract : Obesity is a common yet multifactorial issue for people with psoriasis due to the unique psychological challenges which they face. This systematic review aimed to identify relevant psychosocial issues which are associated with excess weight to inform future intervention studies which aim to look beyond traditional weight loss approaches for weight loss such as low‐calorie diets.